The Criminal Procedure Code: Some Recent Amendments - Abdul Rashid, Talat Mahmood (Journal of Malaysian and Comparative Law, 2019)
The criminal justice system in Malaysia witnessed some significant and far-reaching changes in the later part of 1994 and early 1995. These changes were brought about through amendments to the Federal Constitution, the Criminal Procedure Code (CPC), the Courts of Judicature Act 1964 (CJA), the Subordinate Courts Act 1948 (SCA), and the Kidnapping Act 1961.